Diseño del sistema de alcantarillado sanitario de la localidad de Yarina, distrito de Chipurana, provincia de San Martín, región San Martín - Vásquez Ríos, Rosado (2011)
In his minority the waters of the cities sewer system untreated. With the absence of treatment, sewage are usually dumped into surface waters, creating an obvious risk to human health, ecology and animals. In our country, many streams are recipients of direct discharges of domestic and industrial waste. Soil contamination occurs both in urban and rural areas. The increase in population will continue in the coming decades, as well as pressures on infrastructure in sanitation. Is difficult to generalize about any condition in our country, due to the diversity economic, social and environmental in each region. A major concern is the poor people who live in urban areas and lives in colonies and areas that are unsuitable for development (such as steep slopes of hills and swamps, Plains prone to flooding). In our country, there is a division marked the populations of e....